Bioactive triterpenes from Diospyros blancoi - Ragasa, Consolacion Y. (Animo Repository, 2009)
The ethyl acetate extract of the air-dried leaves of Diospyros blancoi afforded isoarborinol methyl ether (1), a mixture of -amyrin palmitate, -amyrin palmitoleate, -amyrin palmitate and -amyrin palmitoleate (2) in a 13 : 4 : 3 : 1 ratio, and squalene. The structures of 1, 2 and squalene were elucidated by extensive 1D and 2D NMR spectroscopy. Compounds 1 and 2 exhibited antimicrobial activity against Escherichia coli, Pseudomonas aeruginosa, Candida albicans, Staphylococcus aureus and Trichophyton mentagrophytes, and were found inactive against Bacillus subtilis and Aspergillus niger. Sample 2 exhibited significant analgaesic and anti-inflammatory activities.